HLA-A, -B, -C, -DRB1, -DQA1, and -DQB1 allele and haplotype frequencies defined by next generation sequencing in a population of East Croatia blood donors - Tokić, Stana; Žižkova, Veronika; Štefanić, Mario; Glavaš-Obrovac, Ljubica; Marczi, Saška; Samardžija, Marina; Sikorova, Katerina; Petrek, Martin (Scientific reports, 2020)
Next-generation sequencing (NGS) is increasingly used in transplantation settings, but also as a method of choice for in-depth analysis of population-specific HLA genetic architecture and its linkage to various diseases. With respect to complex ethnic admixture characteristic for East Croatian population, we aimed to investigate class-I (HLA-A, -B, -C) and class-II (HLA-DRB1, -DQA1, -DQB1) HLA diversity at the highest, 4-field resolution level in 120 healthy, unrelated, blood donor volunteers. Genomic DNA was extracted and HLA genotypes of class I and DQA1 genes were defined in full-length, -DQB1 from intron 1 to 3' UTR, and -DRB1 from intron 1 to intron 4 (Illumina MiSeq platform, Omixon Twin algorithms, IMGT/HLA release 3.30.0_5). Linkage disequilibrium statistics, Hardy-Weinberg departures, and haplotype frequencies were inferred by exact tests and iterative Expectation-Maximization algorithm using PyPop 0.7.0 and Arlequin v3.5.2.2 software. Our data provide first description of 4-field allele and haplotype frequencies in Croatian population, revealing 192 class-I and class-II alleles and extended haplotypic combinations not apparent from the existing 2-field HLA reports from Croatia. This established reference database complements current knowledge of HLA diversity and should prove useful in future population studies, transplantation settings, and disease-associated HLA screening.
Keywords: dospělí; Humans; běloši; lidé středního věku; Gene Frequency; Middle Aged; HLA-A antigeny; Sequence Analysis, DNA; mladý dospělý; Linkage Disequilibrium; dárci krve; Croatia; zdraví dobrovolníci pro lékařské studie; HLA-A Antigens; mužské pohlaví; HLA-DQ alpha-Chains; vysoce účinné nukleotidové sekvenování; Adult; Chorvatsko; High-Throughput Nucleotide Sequencing; HLA-DQ beta řetězec; frekvence genu; HLA-DQ beta-Chains; vazebná nerovnováha; HLA-B Antigens; ženské pohlaví; HLA-C antigeny; sekvenční analýza DNA; White People; HLA-DRB1 řetězec; HLA-DRB1 Chains; Blood Donors; HLA-B antigeny; lidé; HLA-C Antigens; Male; Young Adult; HLA-DQ alfa řetězec; Haplotypes; haplotypy; Healthy Volunteers; Female